Neuropharmacological profile of the butanolic fraction obtained from leaves of cecropia peltata l. (2013)
The butanolic fraction obtained from the extract of Cecropia peltata L (NV: "Yarumo"), medicinal plant used by popular tradition in Colombia as tranquilizer, displays in ICR albino mice an anticonvulsant, anxiolytic and sedative profile, according to electroshock, pentylenetetrazole, marble burying and barbiturate sleeping tests (80 mg/kg, p. o., p = 0.05 vs. control). At the same time Cecropia peltata does not to seem to alter the locomotor function nor to have antidepressant effect, according to their effect in wiring and forced swimming tests. The effect of this fraction was greater than ethanolic, aqueous and hexanic fractions. Additionally, a sub-fraction from butanolic part, rich in flavonoids, elicits a "dose-response" effect in maximum electroshock-induced seizures (80 - 240 mg/kg). These findings suggest that flavonoid metabolites play a key role in the pharmacological activity of Cecropia peltata and support the traditional use of this species.